Demystifying the fears and myths: The co-production of a regional food, energy, water (FEW) nexus conceptual model. Issue 132 (June 2022) - Tilt, Jenna H.; Mondo, Holly A.; Giles, Nick A.; Rivera, Samuel; Babbar-Sebens, Meghna
Abstract: The food, energy, and water (FEW) sectors are heavily impacted by increasing vulnerability of natural resources. The concept of a FEW Nexus highlights resource interdependencies and the need for integrated decision making across FEW sectors. The objective of this paper is to identify how regional-scale FEW stakeholders in the Umatilla Basin, OR USA perceive the FEW Nexus and to co-produce a FEW Nexus conceptual model aimed to aid regional decision support. A five-stage qualitative stakeholder engagement process, which included the development of futures scenario narratives, allowed FEW stakeholders and researchers to learn from one another and recognize opportunities to adaptively manage FEW resources, particularly when faced with chronic and acute stresses in the region. The resulting conceptual model integrates individual FEW sub-sector adaptive management actions and identifies impacts from these actions to other FEW sub-sectors, compensating for different timescales and trigger points. The visualization of resource management actions and impacts via the conceptual model increased communication among FEW stakeholders and provided a structural framework for a decision support tool currently being developed for the region. While the conceptual model is based on a regional FEW Nexus, this nexus is heavily influenced by global forces particularly agricultural trade, transboundary water negotiations, changing climate conditions, and interstate energy production. Thus, the resulting conceptual model can be adapted from hyper-local to global because its modular design allows researchers and stakeholders to decide which sectors to include depending upon salient FEW issues and scales. Highlights: Food, Energy, Water (FEW) Nexus requires understanding resource interdependencies. Identifying FEW interdependencies and challenges occur with stakeholder engagement. Visualization of FEW Nexus connections increases understanding of shared interests. Conceptualizing the FEW Nexus must account for multiple spatial and temporal scales. A FEW Nexus conceptual model can open opportunities for adaptive governance.